Graduate experiences with transnational nursing education: a qualitative enquiry. Issue 3 (15th April 2019) - Naidoo, Vasanthrie; Sibiya, Maureen Nokuthula
Abstract : Purpose: The purpose of this paper is to share insights, research findings and discuss key issues related to graduate experiences with transnational nursing education (TNE). Design/methodology/approach: The authors used a qualitative approach and sampled national and international nurse graduates to identify challenges and best operating practices in cross-border nursing program facilitation. Findings: This research paper has provided a platform for graduates to lend their voices to the promotion of effective cross-border nursing education delivery and suggests that although international collaborations endeavor to maintain high academic standards in TNE, there is still a need to re-engineer, revise and adapt curricular content, learning, teaching and assessment practices to aid the nursing student. Research limitations/implications: Identified challenges affecting the facilitation and delivery of cross-border nursing education programs can act as levers to improving service quality of present and future cross-border programs to the nursing student. This will assist future nursing students to recognize culture shock and embrace their decision to pursue nursing. Practical implications: The experience of being involved in TNE for nursing students may not be that much different than students of other disciplines. While not able to be generalized to the entire population, the reports by the nursing students in this sample appear to be valuable and worthwhile to continue supporting and encouraging other TNE opportunities. Originality/value: This paper explores cross-border nursing education experiences from national and international perspectives. The authors were able to explore inherent TNE challenges from diverse population and cultural backgrounds.